Overview of Innovations in Geotechnical Engineering - Wijeyesekera, Devapriya Chitral (International Journal of Integrated Engineering, 2014)
This paper outlines some historical and current innovative concepts that underpin the developments in geotechnical engineering. The far reaching aim is to inspirationally encourage further innovation in that innovation need not necessarily be entirely new and unique ways of doing things. Accordingly, the lessons from the historical development, bio mimicry and emerging concepts are illustratively presented. The importance of creating added value to projects through innovation is endorsed. A number of examples based on the author’s research and experience, ranging widely across the themes of the conference are presented.. In many ways geotechnology has reached maturity over the last century, but some scenarios continue to remain as challenging engineering problems. In the recent times, geotechnical engineering finds benefit in being at the crossroads with the advancements in high-tech solutions and the expanding geo technology applications, and in multi disciplinary collaborations with nanotechnology, biotechnology and information technology. The goal of innovative geo engineering research must provide effective solutions in both short and long term, with knowledge and understanding to solve problems with more sustainable certainty